Clinical evaluation of uncaria tomentosa in the treatment and control of lesions caused by herpes simplex infection - Gama, Carlos Romualdo B.; Passos, Mariana D.L.; Varella, Rafael; Lasmar, Ricardo; Gama, Gustavo F.; Oliveira, Lisa; Daher, João Gabriel L.; Passos, Mauro Romero L.; Geller, Mauro (Brazilian Journal of Sexually Transmitted Diseases, 2010)
Introduction: infections caused by herpes simplex viruses represent one of the most common sexually transmitted diseases globally, and account for a broad spectrum of clinical involvement. Uncaria tomentosa is a plant commonly known as cat’s claw, the extracts of which are widely used for its pharmacological properties, which include beneficial effects on allergies as well as anti-inflammatory, antimicrobial, and antioxidant activity. Objective: the overall objective of this study was to evaluate the topical use of Uncaria tomentosa extract in the form of a 50mg/g gel as an adjuvant in the treatment and control of oral and genital lesions resulting from infection by herpes simplex. The specific objectives were to evaluate the efficacy and safety of the use of topical Uncaria tomentosa extract in the treatment and control of oral and genital lesions resulting from infection by herpes simplex, through clinical assessments of the herpetic lesions and questionnaires answered by the patients and the investigating physician; physical examination; incidence of adverse events; and incidence of changes in laboratory exam parameters. Methods: an open study in patients presenting lesions resulting from HSV-1 or HSV-2 infection, treated with Uncaria tomentosa extract in the form of a 50 mg/g topical gel, during a minimum of 5 days and a maximum of 10 days. The efficacy assessments were performed using data collected prior to treatment (pretreatment), after 5 days of treatment (visit 2), and after 10 days of treatment (final visit). Primary efficacy measures included cure (defined as loss of the hard crust) of the lesions and presence of pain and pruritis in the lesions. Secondary efficacy measures included the presence of edema and/or rubor in the lesions, and the incidence of new lesion development during the treatment period, as well as the Physician’s Assessment, the Patient’s Assessment, and the Global Efficacy Assessment. Overall clinical tolerability and safety were analyzed by: the incidence of all adverse events; serious adverse events and/or hospitalizations; abstinence syndromes due to any adverse event; incidence of clinically significant alterations in laboratory tests, as well as the Global Safety Assessment. The results were compared for each evaluation (pretreatment/visit 2/ visit 3). Results: a total of 150 patients were included in the analysis. After 5 days of treatment (visit 2), 45 (30%) presented complete lesion healing, and were considered therapeutic successes. After 10 days of treatment, 69 (68.3%) of the 101 patients who remained in treatment presented total lesion healing. There was a statistically significant reduction in the percentage of patients presenting pain at visit 2 (p < 0.0001) and at visit 3 (p < 0.0001), and statistically significant reductions (p < 0.0001 for all) in the percentage of patients presenting pruritis, edema and burning at visit 2 and visit 3. At visit 3, there was a statistically significant reduction (p = 0.0032) in the percentage of patients presenting rubor. No changes in vital signs were recorded at visit 2 and at visit 3, in relation to pretreatment values. Adverse events (EAs) were registered in 10 patients; these were classified as mild or moderate in intensity, and transitory. In the patient’s assessment carried out at the final visit, 70 patients (69.3%) responded to the assessment with scores of 8-10. In the Physician’s assessment carried out during the final visit, 66 patients (65.3%) received scores of 8-10. In the Global Efficacy Assessment performed by the investigating physician, efficacy was deemed Very Good in 57 patients (38.3%). In the Global Safety Assessment performed by the investigating physician at the end of the treatment period, tolerability of the medication was considered Very Good in 81 (54.4%) of the patients. Conclusion: Based on the results obtained with this evaluation, we conclude that Uncaria tomentosa extract in the form of 50 mg/g gel was safe and effective in the treatment and control of the oral and genital lesions resulting from HSV-1 and HSV-2 infection, in the patient population evaluated.